2019
DOI: 10.1002/rnc.4572
|View full text |Cite
|
Sign up to set email alerts
|

Guaranteed‐performance consensus design for Lipschitz nonlinear multiagent systems with jointly connected topologies

Abstract: Guaranteed-performance consensualization problems for both leaderless and leader-following multiagent systems with jointly connected topologies and Lipschitz nonlinear dynamics are investigated. To achieve the guaranteedperformance consensus, the control protocols and quadratic performance functions based on state errors are proposed. The state error method is utilized to deal with the guaranteed-performance consensualization problems for both leaderless and leader-following cases. Then, the Lipschitz nonlinea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…Third, the constraints (4) and (5) in Assumption 3 can be replaced by the following stricter constraints:…”
Section: Lemmamentioning
confidence: 99%
See 1 more Smart Citation
“…Third, the constraints (4) and (5) in Assumption 3 can be replaced by the following stricter constraints:…”
Section: Lemmamentioning
confidence: 99%
“…Generally, consensus problem of multiagent networks refers to choosing a control protocol, which depends on relative information among the state of the agents, such that the agents reach consensus (including asymptotic consensus and finite time consensus). [5][6][7][8][9] For this purpose, various kinds of control protocols have been proposed for different kinds of agents. Notice that, for multiagent networks with linear dynamics, this is a well researched area.…”
Section: Introductionmentioning
confidence: 99%
“…Ren addressed formation control problems by implementing the consensus‐based approach and showed that the above‐mentioned classical methodologies could be unified in the framework of the consensus‐based formation control. Inspired by the development of the consensus theory in the control community, the newly developed consensus‐based formation control strategies were reported in many application fields including mobile robots, intelligent ground vehicles, and unmanned aerial vehicles (see References and the references therein).…”
Section: Introductionmentioning
confidence: 99%
“…The consensus problem of multiagent systems (MASs) has drawn great attention due to its broad applications in many areas such as formation control of robotic teams, information fusion of sensor networks, attitude alignment of multiple unmanned aerial vehicles, and so on . In the past decade, many works have been represented to address the consensus control problem for linear or affine nonlinear MASs (see, for example, References ). However, in some applications such as the chemical reaction, the pendulum control, and the wind turbine control, the dynamic models of systems are in nonaffine form such that the control input does not appear linearly, which makes the controller design more difficult and challenging than affine systems.…”
Section: Introductionmentioning
confidence: 99%